Analisis Standar Kompetensi Tenaga Kesehatan di Rumah Sakit Bhakti Yudha Depok Tahun 2017 - Silviana, Syifa (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
Competency of healthcare provider has significant impact on performance of the hospital. Measuring competency of healthcare provider are essential to improve better quality of service provisioned. The study evaluates competency of healthcare provider at Bhakti Yudha Hospital by using the competency standards established by multiple organizations of Indonesian national healthcare provider association mapped against eight units of health provider. The result stated that competency level of healthcare providers at Bhakti Yudha Hospital have had not met the expectations. It is concluded that working experiences and number of relevant training received has significant impact on competency level of healthcare provider.